Antineutrophil Cytoplasmic Antibody-Associated Vasculitis Update: Genetic Pathogenesis - Li, Weiran; Huang, He; Cai, Minglong; Yuan, Tao; Sheng, Yujun (Frontiers in Immunology, 2021)
Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is characterized by the inflammation of small and medium vessels and presence of proteinase 3-ANCA or myeloperoxidase-ANCA in the circulation. AAV comprises three clinical subtypes: granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), and eosinophilic GPA (EGPA). Although the pathogenesis of AAV is still unclear, genetic and environmental factors and the immune system are thought to be involved. Genetic factors have been confirmed to play an important role in AAV. Genome-wide association studies have identified numerous genetic variants in MHC and non-MHC regions associated with AAV. The strongest evidence of MHC association in AAV is human leukocyte antigen (HLA)-DP. A significant association between AAV and genetic variations in non-MHC regions, such as CTLA-4, FCGR2A, PTPN22, SERPINA1, and TLR9 has also been found. Moreover, different clinical subtypes of AAV have distinct genetic backgrounds. GPA is associated with HLA-DP1, MPA with HLA-DQ, and EGPA with HLA-DRB4. These findings could help elucidate the etiology of AAV and develop new biomarkers for diagnosis and targeted therapy. Herein, we briefly summarize the updates on the genetic pathogenesis and biomarkers of AAV.